Effects of health empathy map on physician’s empathic behavior perceived by the patient - Cançado, Paula (2021)
The objective of this study was to investigate the effect of Health Empathy Map (HEM) on patient’s perception of physician’s empathic behavior. This was a 3-phase experimental study, conducted with 22 orthopedic residents. In the first phase, the residents’ empathic and relational skills was assessed by patients at the orthopedics outpatient clinic, using the Consultation and Relational Empathy Measure (CARE). After a training session (2nd phase), the HEM was implemented by residents in outpatient care for 4 weeks. One week later the interruption of HEM (3rd phase), the CARE scale was again applied to patients. The results showed significant improvement in residents’ patient-rated empathy scores, suggesting that the HEM improved the empathic behavior. These findings indicate that HEM can be considered as an auxiliary strategy for empathic skills development.